Analisis Pengaruh Dana Desa Terhadap Kemiskinan di Nusa Tenggara Timur - Demarce Sabuna; Kadir Ruslan (Badan Pusat Statistik Provinsi NTT, 2023)
The priority of the Village Budget usage is to finance community development and empowerment aimed at improving the welfare of rural communities, improving the quality of human life and reducing poverty. The Village Budget has been utilized in East Nusa Tenggara Province since 2015. As a region with the third highest percentage of the poor in Indonesia, the Village Budget have a negative impact on reducing poverty rate. This study aims to determine the effect of the Village Budget on reducing poverty rate in East Nusa Tenggara. This study is using variables such as the Human Development Index, the Unemployment Rate and Gross Regional Domestic Product that assumed to have effect on the poverty rate. Panel data regression analysis with random effect model concluded that the Village Budget disbursed by the government to all districts in East Nusa Tenggara have little to no effect in reducing the number of the poor in 2016-2022. The Human Development Index and Gross Regional Domestic Product variables contribute significantly to reduce poverty while the Unemployment Rate variable has not. Inefficient management of the Village Budge caused by corruption of the Village Budget, low human resources of Village Officials, lack of supervisions are acting as the main causes of why the poverty rate in East Nusa Tenggara is barely reduced. Keywords: Village Budget, Human Development Index, GDRP, Unemployment, Poverty